The Predictive Value of Fragmented QRS for Cardiovascular Events in Acute Myocardial Infarction: A Systematic Review and Meta-Analysis - Luo, Gongming; Li, Qian; Duan, Jingwei; Peng, Yu; Zhang, Zheng (Frontiers in Physiology, 2020)
Objective: Fragmented QRS (fQRS) has been reported as a predictor of major adverse cardiac events (MACE) and mortality in several studies on cardiovascular disease. However, most studies have yielded discrepant results. This study aimed to explore the correlation between fQRS and cardiovascular events in patients with acute myocardial infarction (AMI) during the hospital stay and follow-up period and the predictive value of fQRS in the prognosis of AMI. Methods: We searched for relevant studies in four databases, Medline, Embase, PubMed, and Cochrane Library from January 2010 to March 2020. Our initial search yielded 585 articles. Of these, we screened 20 studies, and finally included a total of 7138 patients in this analysis comparing death events or MACE in AMI patients with or without fQRS. Results: Fragmented QRS was significantly associated with a higher risk of in-hospital mortality (OR, 3.97; 95% CI, 2.45-6.44; p<0.00001), long-term mortality (OR, 2.93; 95% CI, 1.76-4.88; p<0.0001), in-hospital MACE (OR, 2.55; 95% CI, 1.80-3.63; p＜0.00001), and long-term MACE (OR,3.81;95%CI,2.21-6.57;p<0.00001).In particular, it demonstrated a higher predictive value for in-hospital cardiovascular mortality and long-term all-cause mortality in AMI patients and in-hospital mortality in patients with ST-segment elevation myocardial infarction (STEMI). Moreover, fQRS was also associated with an increased risk of ventricular arrhythmias (OR, 2.76; 95% CI, 1.72-4.43; p<0.0001) and heart failure (OR, 1.65; 95% CI, 1.02-2.66; p=0.04). Fragmented QRS was negatively associated with left ventricular ejection function(LVEF) (MD, -5.22; CI:[-6.75,-3.69]; p<0.00001) and positively associated with a high incidence of coronary artery triple vessel lesions (OR, 2.14; 95% CI, 1.31-3.51; p＝0.002) in AMI patients. Conclusion: Fragmented QRS is significantly associated with in-hospital and long-term mortality and MACE in patients with AMI, as well as ventricular arrhythmias and heart failure. Furthermore, it may be suited as a marker of mortality and MACE risk. Moreover, fQRS also indicates a reduced LVEF and a high incidence of coronary artery triple vessel lesions in AMI patients.